Gelatinous Drop-Like Corneal Dystrophy in an Acehnese Family: Serial Cases.: Poster Presentation - Case Series - Ophthalmologist - Samira, Cut Putri; Akbar, Muhammad Khalil (Majalah Oftalmologi Indonesia, 2023)
Introduction : Gelatinous drop-like dystrophy (GDLD) is a rare type of corneal dystrophy with an autosomal recessive inheritance pattern. Although the prevalence in Japan is approximately 1 in 33,000, it is much less common in other nations. Lamellar or penetrating keratoplasty is needed for most patients to alleviate the symptoms. This case series aims to provide knowledge regarding rare cases of GDLD and its management. Case Illustration : Three male siblings from consanguineous marriage were found to have corneal dystrophy, characterized by a white-yellow nodular lesion with a kumquat-like appearance on the corneal surface. The visual acuity of each patient was light perception with good projection. To treat the condition, all patients underwent full-thickness penetrating keratoplasty. One month after the procedure, their visual acuity had improved to 3/60, 2/60, and 2/60, respectively. Discussion : GDLD is a genetic disease with gelatinous amyloid deposits in the cornea that typically manifests within the first decades of life. GDLD can present in three different phenotypes, including band keratopathy, mulberry, and kumquat-like appearance. In the case of these siblings, they have developed the severe kumquat-like phenotype. Detection by examining family involvement and the cornea's clinical presentation can help diagnose GDLD. Full-thickness penetrating keratoplasty can be an option for managing severely impaired visual acuity caused by GDLD. Conclusion : GDLD is a rare corneal dystrophy that can lead to severe visual impairment. The objective of treating GDLD is to enhance vision and prevent its progression. Vision loss can be alleviated througha surgical procedure such as full-thickness penetrating keratoplasty.